PENGARUH INTERNET FINANCIAL REPORTING (IFR) TERHADAP NILAI PERUSAHAAN, HARGA SAHAM, DAN FREKUENSI PERDAGANGAN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA) - Siti Nurlatifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to determine the effect of Internet Financial Reporting (IFR) on company value, stock prices, and stock trading frequency (Empirical Study of Mining Companies on the Indonesia Stock Exchange). This study uses a quantitative descriptive approach, aiming to determine the relationship between two or more variables. The data used is secondary data, namely financial reports and annual reports downloaded from the IDX's official website, namely www.idx.co.id. The population of this study is Mining Companies listed on the Indonesia Stock Exchange in 2017-2019 with a total of 44 companies. Samples were taken using a purposive sampling technique totaling 10 companies in 3 years to produce 30 units of analysis. Data analysis techniques used SPSS version 25 in the form of descriptive statistics and simple regression analysis. The test results show that Internet Financial Reporting (IFR) is empirically proven to have a positive and significant effect on firm value, Internet Financial Reporting (IFR) is empirically proven to have a positive and significant effect on stock prices, Internet Financial Reporting (IFR) has no significant effect on stock trading frequency. The novelty of this study answers the gaps of previous research, using different variables from previous researchers and a different time span from previous years.